2018
DOI: 10.1007/s00261-018-1478-3
|View full text |Cite
|
Sign up to set email alerts
|

Splenic contraction: a new member of the hypovolemic shock complex

Abstract: Decreased splenic volume is a ubiquitous and reliable sign of hypovolemic shock and should be considered a member of the hypovolemic shock complex. It is of particular utility when a prior study is available. Splenic hypoenhancement has high specificity and a high positive predictive value for hypovolemic shock in the correct patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
0
12
0
3
Order By: Relevance
“…Enslow et al reported that 71 trauma patients had significantly smaller spleens than healthy controls (107 AE 63 cm 3 vs. 220 AE 164 cm 3 ). In addition, 34 of 35 patients had a 30% greater reduction in spleen volume when in shock than in pre-shock (Enslow et al, 2018). There are two mechanisms by which organ size is reduced during hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 98%
“…Enslow et al reported that 71 trauma patients had significantly smaller spleens than healthy controls (107 AE 63 cm 3 vs. 220 AE 164 cm 3 ). In addition, 34 of 35 patients had a 30% greater reduction in spleen volume when in shock than in pre-shock (Enslow et al, 2018). There are two mechanisms by which organ size is reduced during hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 98%
“…It also interacts with the kidneys and mesenteric vascular bed via nervous and hormonal regulation, 8 and contracts in response to adrenergic stimulation in a state of sympathetic nerve hyperactivity, such as during hypovolemic shock or hemorrhagic shock. 9,10…”
Section: Discussionmentioning
confidence: 99%
“…In the event of a circulatory shock, the spleen fulfills its reservoir function by reducing the arterial inflow and increasing the venous outflow [1]. In this context, Enslow et al demonstrated a decrease in volume and an associated reduction of the spleen's density values [15]. Moreover, a decreased splenic enhancement in the arterial phase may be a mortality predictor in patients with hypovolemic shock [14].…”
Section: Discussionmentioning
confidence: 99%
“…The adrenal-to-IVC ratio was defined by the mean radiodensities of adrenal glands divided by the IVC's radiodensity. The splenic attenuation value was obtained by placing three circular ROIs (2.0 cm 2 in size) at three different axial levels through the superior third, middle third, and inferior third of the spleen in portal venous phase [15]. Hypodense triangular wedge-shaped areas at the periphery of the spleen were not included in the measurement.…”
Section: Image Analysismentioning
confidence: 99%